Development of Multi-dimensional Scale to Measure Attitude of Farmers Towards Conservation Agricultural Practices - Tannishtha Bardhan,; Neelam Bhardwaj,; Shivendra Kumar Kashyap,; V. L. V. Kameswari,; Govind Singh Kuswaha,; Abir Dey, (Indian Journal of Extension Education, 2022)
Attitude exhibits a pivotal role in influencing one’s behaviour towards any psychological object. The present study aimed at developing and validating a multi-dimensional attitude scale on Conservation Agricultural practices based on Maheshwari–Kumar–Jhamtani– Bhaskaran–Dandapani (M-K-J-B-D) method. The steps included item collection, item selection, item analysis, conducting Principal Component Analysis to extract the underlying dimensions and finally calculation of attitude scores. A total of 75 attitudinal items were pooled initially covering various aspects of Conservation Agriculture (CA) and were subjected to item relevancy checking and item analysis. The final scale contained 25 attitudinal statements under eight sub-dimensions. The reliability of the scale was measured by using Cronbach’s Alpha and the reliability coefficient was found to be 0.80 which was satisfactory. The validity was assessed using content validity method by dispensing the finalized scale to 10 subject related experts. This standardized scale can be used by other academicians of related fields with or without modifications to measure attitude of farmers towards different aspects of Conservation Agriculture.